The use of inactivated brain homogenate to determine the in vitro fraction unbound in brain for unstable compounds. (2nd October 2020) - Nirogi, Ramakrishna; Molgara, Parusharamulu; Bhyrapuneni, Gopinadh; Manoharan, Arunkumar; Padala, Nagasurya Prakash; Palacharla, Veera Raghava Chowdary
Abstract: The use of IBH-5 decreased the k deg values and increased the half-life of the compounds PNZ, TCP, Cpd I and Cpd II with k deg values of 1.10 × 10 −4  s − 1 ( t 1/2 = 115 min), 4 × 10 −5  s −1 ( t 1/2 = 289 min), 4 × 10 −5  s −1 ( t 1/2 = 289 min), and 3 × 10 −5  s −1 ( t 1/2 = 385 min) respectively, compared to k deg values of 1.25 × 10 −2  s −1 ( t 1/2 = 0.9 min), 1.1 × 10 −4  s −1 ( t 1/2 = 105 min), 1.0 × 10 −3  s −1 ( t 1/2 = 11.5 min) and 4.5 × 10 −4  s −1 ( t 1/2 = 26 min) in FBH The use of lower temperature (4 °C) for the determination of f u, brain in this study is not successful due to the instability of the compounds during longer equilibration times required at lower temperatures. The f u, brain values for a set of 15 CNS drugs determined in FBH and IBH-5 using HT-dialysis were similar and are consistent with the literature values. The use of IBH-5 led to the determination of f u, brain for unstable compounds that could not be determined by other methods. The use of IBH-5 is an easy and convenient method to determine the f u, brain of unstable compounds in FBH during drug discovery and development.